Specific Features of Magnetic Storms on the Cardiovascular System - Khodjamberdiev Akram Ilkhamjanovich (Central Asian Journal of Medical and Natural Science, 2022)
The Earth's magnetic field and its variations resulting from the influence of solar activity on the ionosphere of the planet belong to natural magnetic fields. A permanent geomagnetic field is generated by currents in a liquid metal core, and varies depending on geographical latitude.